The relationship between standard of living and quality of life for older New Zealanders : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Wellington, New Zealand - Graham, Stewart Edwin (Massey University, 2015)
The well-being of older people is an increasingly important issue. This is due to both the increasing proportion of older people in the population and rising levels of inequality in New Zealand. What well-being is and what influences well-being is an important question when considering the welfare of older people. Standard of living and quality of life offer two different ways of understanding well-being. It is vital to understand the impact that changing standard of living has on older people’s quality of life. The aim of this study was to explore the relationship between standard of living and quality of life and consider the impact of other factors on quality of life for older people in New Zealand. This study is a secondary analysis of data from the 2012 wave of the New Zealand Longitudinal Study of Ageing. This study includes 2984 people aged between 50 and 87 years of age. Bivariate and hierarchical multiple regression analysis was employed to explore the relationship between standard of living, quality of life, health-related variables (physical health, mental health, depression, mobility and loneliness) and demographic variables. Results revealed two main findings. Firstly, that a low standard of living does not preclude a high quality of life, but a high standard of living means a low quality of life is less likely. Secondly, the relationship between standard of living and quality of life is mediated by health-related variables. Psychological health-related variables (mental health, depression and loneliness) mediated the relationship more than physical health-related variables (physical health and mobility). These demonstrate that although a high standard of living is not a prerequisite for a high quality of life, it can potentially provide a buffer against factors which cause poor quality of life such as poor physical and mental health. Increases in standard of living for older people can therefore act to mitigate key factors contributing to poor quality of life. These findings have important implications for future policy development in relation to the welfare of older New Zealanders.
Keywords: Quality of life; Cost and standard of living; Older people; Psychology; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology